Physiological correlates of competitive performance in portuguese elite middle distance runners - Reis, J.; Manuel, B.; Reis, V. M.; Almeida, T.; Vleck, V.; Alves, F. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Middle distance performance in running is dependent on the ability of deriving high amounts of muscle power from both the aerobic and the anaerobic metabolic energy systems. The purpose of this study was to identify the physiological correlates of the 1500 m performance in elite middle distance Portuguese runners. Methods: All tests were completed two to five days after the main races of the season where every athlete ran the 1500m event. The time obtained was registered as the season best time (SBT). 28 national and international level male Portuguese middle distance runners (SBT: 3:45.20±5.8 min:s) participated in this study (age: 24.1±3.9 yr.; body mass: 64.5 ± 5.8 kg; height: 177.5 ± 7 cm). All tests were conducted on a standard 400-m outdoor athletics track. Subjects initially completed an incremental test of 5x6 min duration and constant velocity steps, in order to estimate submaximal energy cost of running, VO2peak and maximal aerobic velocity (MAV) and lactate threshold. In a subsequent session, a supramaximal test of 600 m was performed, to complete the estimation of maximal anaerobic oxygen deficit (MAOD) and to analyze VO2 on-kinetics. Time constant of the primary phase (tau) and amplitude were calculated using a mono-exponential model. Respiratory data was collected breath by breath (K4b2, Cosmed, Italy) and blood lactate concentrations were measured with the Lactate Pro LT-1710 analyser (Arkray KDK). Results: Only MAV (5.73 ± 0.46 m/s) showed a significant correlation with the 1500 m race performance (r=0.40; p.0.05). VO2peak (65.43 ± 6.33 ml/kg/min) showed a small interindividual variability (coefficient of variation= 9.7 %), contrarily to MAOD (34.61 ± 11.23 mlO2/kg; coefficient of variation=32.4 %). In spite of this, MAOD was poorly related to SBT (r2=0.16). However, the five best race time runners showed MAOD values lower than the average of the total group (26.04 ± 8.35 mlO2/kg). On the other hand, MAOD was negatively correlated with MAV (r=0.42; p.0.05), confirming the tendency for lower anaerobic capacity in the faster 1500 m runners. Supramaximal tau(9.62 ± 2.21s) was negatively associated to VO2peak (r=. 0.60; p.0.05). Discussion: Best middle distance Portuguese runners, in spite of a good international competitive level, have a markedly aerobic profile, possibly lacking muscle power and sprint adaptations. VO2 on-kinetics time constant, measured in a supramaximal track running test of 600 m, was not confirmed as a predictor of 1500 m performance. The fast VO2 responses observed, however, when compared with data from different training status age matched populations (Bosquet et al., 2007), in similar duration and intensity exercises, indicate that this parameter is influenced by aerobic training.